2009
DOI: 10.1152/ajpregu.90585.2008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and postweaning diet interaction alters hypothalamic gene expression and modulates response to a high-fat diet in male offspring

Abstract: Page KC, Malik RE, Ripple JA, Anday EK. Maternal and postweaning diet interaction alters hypothalamic gene expression and modulates response to a high-fat diet in male offspring. Am J Physiol Regul Integr Comp Physiol 297: R1049 -R1057, 2009. First published August 5, 2009 doi:10.1152/ajpregu.90585.2008.-Epidemiological data and results from animal studies indicate that imbalances in maternal nutrition impact the expression of metabolic disorders in the offspring. We tested the hypothesis that consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
82
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 44 publications
12
82
0
8
Order By: Relevance
“…The origin of other metabolic diseases in the adult can be also related with maternal overnutrition, such as hypertension and hyperlipidemia (Elahi et al, 2009) or insulin resistance and diabetes (Samuelsson et al, 2008), and maternal HFD is associated with changes in hypothalamic regulation of body weight and energy homeostasis by altering the expression of leptin receptor, proopiomelanocortin, and neuropeptide Y in the adult offspring (Page et al, 2009). Nevertheless, not all the studies arise to the same conclusion.…”
Section: Hypercaloric and High-fat Dietsmentioning
confidence: 99%
“…The origin of other metabolic diseases in the adult can be also related with maternal overnutrition, such as hypertension and hyperlipidemia (Elahi et al, 2009) or insulin resistance and diabetes (Samuelsson et al, 2008), and maternal HFD is associated with changes in hypothalamic regulation of body weight and energy homeostasis by altering the expression of leptin receptor, proopiomelanocortin, and neuropeptide Y in the adult offspring (Page et al, 2009). Nevertheless, not all the studies arise to the same conclusion.…”
Section: Hypercaloric and High-fat Dietsmentioning
confidence: 99%
“…In addition, leptin programming in utero might influence the food intake regulatory system throughout life. The offspring of dams fed a high-fat diet during gestation were heavier and concomitantly had higher hypothalamic mRNA expression of leptin receptors, proopiomelanocortin, and neuropeptide Y [38]. Vogt et al [39] showed that abnormal insulin signaling in murine progeny caused by high-fat diet feeding of dams interferes with the formation of the hypothalamic neural circuits that contribute to metabolic status.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a reduction in the catalytic subunit p85a of PI3K enhances insulinstimulated Akt activity (34). It was reported that PI3K subunit p85a was upregulated in the hypothalamus of mice that were exposed to an HFD throughout IU/L and the first 120 days of life (35). HFD-induced obesity was shown to require activation of PI3K-dependent hypothalamic pathways (36).…”
Section: Discussionmentioning
confidence: 99%